Limited evidence of chondrocyte outgrowth from adult human articular cartilage. Issue 1 (January 2016) - Zingler, C.; Carl, H.-D.; Swoboda, B.; Krinner, S.; Hennig, F.; Gelse, K.
Summary: Objective: Cellular outgrowth from articular cartilage tissue has been described in a number of recent experimental studies. The aim of this study was to investigate the occurrence of cellular outgrowth from articular cartilage explants isolated from adult human donors. Method: Macroscopically intact articular cartilage specimens were isolated from adult human donors and cultured either in their native status, or in a cleansed status achieved by forced washing to minimize attaching cells. Additionally, the effect of chemotactic stimuli including cell lysate, High-Mobility-Group-Protein B1 (HMGB-1), Trefoil-factor 3 (TFF3), bone morphogenetic protein-2 (BMP-2), transforming growth factor-ß1 (TGF-ß1), or three-dimensional fibrin or collagen matrices were investigated. Co-cultures with synovial membrane served as a positive control for a source of migratory cells. The occurrence of cellular outgrowth was analyzed by histological examination after a culture period of 4 weeks. Results: Spontaneous cellular outgrowth from cleansed cartilage specimens was not observed at a relevant level and could not significantly be induced by chemotactic stimuli or three-dimensional matrices either. A forming cartilage-adjoining cell layer was only apparent in the case of native cartilage explants with cellular remnants from surgical isolation or in co-culture experiments with synovial membrane. Conclusion: The relevance of cellular outgrowth from cartilage tissue is largely absent in the case of adult human articular cartilage samples. A cartilage-adjoining cell layer forming around the explants may instead originate from still attaching cells that remained from surgical isolation.